2021
DOI: 10.3389/fnut.2021.622122
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Outbreak in Italy on the Sustainable Food Consumption Intention From a “One Health” Perspective

Abstract: Coronavirus disease (COVID-19) is a transmissible illness that was recognized in December 2019 and World Health Organization (WHO) stated a pandemic on 11 March 2020. As no cure has been developed for COVID-19 disease yet, Italy has adopted restrictive measures to avoid the spread of the virus, causing different psychological reactions (e.g., stress, anxiety) that lead people to change lifestyle and in particular the consumer orientation toward food. In addition, the COVID-19 emergency had also affected the It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 55 publications
4
22
0
7
Order By: Relevance
“…Overall, for all the other aspects, over 30% of the answers are on the last two anchors of the scale. These results are consistent with the study by Castellini et al ( 2021 ) conducted on Italian consumers, which reported an increase in consumers' awareness of the importance of individual responsibility in society, and with the study by Sun et al ( 2021 ) conducted on Chinese consumers, which found that the emotional response induced by the Covid‐19 pandemic has driven consumers to pay more attention to the environment and society.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, for all the other aspects, over 30% of the answers are on the last two anchors of the scale. These results are consistent with the study by Castellini et al ( 2021 ) conducted on Italian consumers, which reported an increase in consumers' awareness of the importance of individual responsibility in society, and with the study by Sun et al ( 2021 ) conducted on Chinese consumers, which found that the emotional response induced by the Covid‐19 pandemic has driven consumers to pay more attention to the environment and society.…”
Section: Resultssupporting
confidence: 91%
“…More than 60% of respondents stated a moderate or extreme increase in the level of awareness. Similar results are reported by Castellini et al ( 2021 ), who highlighted an increase in consumers' awareness of the importance of environmental issues and animal welfare in Italy, as well as by Severo et al (2020), who highlighted an increase in environmental awareness of Brazilian and Portuguese consumers due to the pandemic. In contrast, the study conducted of several European countries by Rousseau and Deschacht ( 2020 ) highlighted that the awareness of environmental issues was not affected.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Another aspect that is missing is the issue of sustainability—a concept that is still vague for Italian consumers ( 76 , 77 )—that is not addressed in AMD and NK questionnaires. As reported by Castellini et al ( 78 ), the COVID-19 pandemic may have been the turning point to raise consumer awareness concerning the close interconnection between human health and ecosystems, supporting the “One Health” perspective and improving a sustainable diet, all of which are aspects of growing importance that need to be included in further similar assessments.…”
Section: Discussionmentioning
confidence: 70%
“…It is confirmed that if consumers are health-conscious, organic food is their first choice [97][98][99]. What is more, in the time of coronavirus, health consciousness is the most relevant driver that boosts the positive attitude towards organic food [97,100]. It can be assumed that the second topic, i.e., food waste, has become the focus of consumers' attention both due to the growing environmental and health consciousness of consumers, as well as some concerns about the economic crisis along with higher food prices caused by the COVID-19 pandemic [101].…”
Section: Discussionmentioning
confidence: 89%